Impact of cancer-associated fibroblasts on survival of patients with ampullary carcinoma - Takagi, Kosei; Noma, Kazuhiro; Nagai, Yasuo; Kikuchi, Satoru; Umeda, Yuzo; Yoshida, Ryuichi; Fuji, Tomokazu; Yasui, Kazuya; Tanaka, Takehiro; Kashima, Hajime; Yagi, Takahito; Fujiwara, Toshiyoshi (Frontiers in Oncology, 2023)
Background: Cancer-associated fibroblasts (CAFs) reportedly enhance the progression of gastrointestinal surgery; however, the role of CAFs in ampullary carcinomas remains poorly examined. This study aimed to investigate the effect of CAFs on the survival of patients with ampullary carcinoma. Materials and methods: A retrospective analysis of 67 patients who underwent pancreatoduodenectomy between January 2000 and December 2021 was performed. CAFs were defined as spindle-shaped cells that expressed α-smooth muscle actin (α-SMA) and fibroblast activation protein (FAP). The impact of CAFs on survival, including recurrence-free (RFS) and disease-specific survival (DSS), as well as prognostic factors associated with survival, was analyzed. Results: The high-α-SMA group had significantly worse 5-year RFS (47.6% vs. 82.2%, p = 0.003) and 5-year DSS (66.2% vs. 93.3%, p = 0.009) than the low-α-SMA group. RFS (p = 0.048) and DSS (p = 0.035) in the high-FAP group were significantly worse than those in the low-FAP group. Multivariate analyses found that high α-SMA expression was an independent predictor of RFS [hazard ratio (HR): 3.68; 95% confidence intervals (CI): 1.21–12.4; p = 0.02] and DSS (HR: 8.54; 95% CI: 1.21–170; p = 0.03). Conclusions: CAFs, particularly α-SMA, can be useful predictors of survival in patients undergoing radical resection for ampullary carcinomas.